Provably secure authentication approach for data security in the cloud using hashing, encryption, and Chebyshev-based authentication. (15th June 2021) - Ahamad, Danish; Akhtar, Md Mobin; Hameed, Shabi Alam; Qerom, Mahmoud Mohammad Mahmoud Al
Secure and efficient authentication mechanism becomes a major concern in cloud computing due to the data sharing among cloud servers and users through the internet. This paper proposed an efficient hashing, encryption, and Chebyshev (HEC)-based authentication in order to provide security among data communication. With the formal and informal security analysis, it has been demonstrated that the proposed HEC-based authentication approach provides data security more efficiently in the cloud. The proposed approach amplifies the security issues and ensures the privacy and data security to the cloud user. Moreover, the proposed HEC-based authentication approach makes the system more robust and secured and has been verified with multiple scenarios. However, the proposed authentication approach requires less computational time and memory than the existing authentication techniques. The performance revealed by the proposed HEC-based authentication approach is measured in terms of computation time and memory as 26 ms, and 1, 878 bytes for 100 Kb data size, respectively.